FROM KKM CLASS TO KC CLASS OF MULTIMAPS - Park, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2022)
This is to give a short history of our multimap classes $\mathfrak{K,\ KC,\ KO}$ in the KKM theory. We show that many authors adopted or imitated the inadequate definition of the KKM class due to Chang and Yen in 1996. We list such works in chronological order and also introduce other works which extended the class properly. Our study on such history will improve the KKM theory in the new millennium.